The Assurance Services of Sustainability Reporting: Preliminary Evidence from a Developing Country - Lau, Chee Kwong; Gan, Ker Sing, Christine (INTI International University, 2018)
In response to the recent introduction of the Business Sustainability Initiatives by the Bursa Malaysia, more listed companies have voluntarily publishing sustainability reports, either stand-alone or integrated with their annual reports. Nevertheless, very little is known about whether these sustainability reports are audited and assured, like their mandatory financial reports, and the assurance practices involved. In this study, we first investigate the availability of assurance statement in sustainability reports issued by the Malaysian publicly listed companies. We then evaluate the content and informativeness of the assurance statements identified. We also ascertain the assurance processes and associated assertions in assurance services rendered on the preparation of the sustainability reports. Though preliminary, our study provides insightful evidence on the assurance practices on sustainability reporting in Malaysia, a developing economy.